A troca racional com Deus: a Teologia da Prosperidade praticada pela Igreja Universal do Reino de Deus analisada pela perspectiva da Teoria da Escolha Racional - Barbieri Junior, Walter (2007)
When we analyze the contemporaneous Brazilian religious camp we can notice great changes in the religious map of the country. At the same time that there is a tendency of reducing the number of affiliations to traditional religions such as catholic and historical protestant, the evangelical churches are spreading around, specially the neopentecostal . One of the main reasons for this change is the use of the Prosperity Theology by the priests of the neopentecostal churches. In this work we propose to build a study of the Prosperity Theology as a success tool used by Igreja Universal do Reino de Deus (IURD) in order to increase the affiliation number. The religious phenomena analyses will be made under a theoretical perspective of Religion Sociology, known as Rational Choice, by Rodney Stark. This theory proposes to apply economical theories and the one of Rational Choice to the religious phenomena, taking into account the existing religious pluralism in Brazil where the presence of a State with freedom of religion guarantees a free market for the companies that offer religious service. In this context, the conditions for a religious exploitation in the country are established and the specialists have to offer a service that meets the customers needs in order to survive the market competition. The analysis takes into account not only the religious demand in the Brazilian religious camp but mainly the offer of religious assets made by IURD specialists